Conformal Dual-band Textile Antenna with Metasurface for WBAN Application - Fatin Nabilah, Giman; Ping, Jack Soh; Mohd Faizal, Jamlos; H., Lago; Azremi Abdullah, Al-Hadi; Mohamedfareq, Abdulmalek; Nidhal, Abdulaziz (Springer Berlin Heidelberg, 2017)
This paper presents the design of a dual-band wearable planar slotted dipole integrated with a metasurface. It operates in the 2.45 GHz (lower) and 5.8 GHz (upper) bands and made fully using textiles to suit wireless body area network applications. The metasurface in the form of an artificial magnetic conductor (AMC) plane is formed using a rectangular patch incorporated with a diamond-shaped slot to generate dual-phase response. This plane is then integrated with the planar slotted dipole antenna prior to its assessment in free space and bent configurations. Simulations and measurements indicated a good agreement, and the antenna featured an impedance bandwidth of 164 and 592 MHz in the lower and upper band, respectively. The presence of the AMC plane also minimized the backward radiation toward the human body and enhanced realized gains by up to 3.01 and 7.04 dB in the lower and upper band.